Changes in long term survival after diagnosis with common hematologic malignancies in the early 21st century - Pulte, Dianne; Jansen, Lina; Brenner, Hermann (Blood cancer journal, 2020)
Five-year survival has increased for many hematologic malignancies in the 21st century. However, whether this has translated into greater long-term survival is unknown. Here, we examine 10- and 20-year survival for patients with multiple myeloma (MM), acute lymphoblastic leukemia (ALL), acute myeloblastic leukemia (AML), chronic lymphoid leukemia (CLL), chronic myeloid leukemia (CML), non-Hodgkin lymphoma (NHL), and Hodgkin lymphoma (HL). Data were extracted from the Surveillance, Epidemiology, and End Results-9 database. Patients age 15+ with the above malignancies were included. The newly developed boomerang method was used to examine 10- and 20-year relative survival (RS) for patients in 2002-2006 and 2012-16. Ten and 20-year RS increased for each malignancy examined, with increases ranging from +4.4% units for 20-year RS for AML to +23.1% units for 10-year RS for CML. Ten year RS was >50% in 2012-16 for patients with CLL, CML, HL, NHL, and DLBCL, at 77.1%, 62.1%, 63.9%, 64.5%, and 63.0%, respectively. Survival dropped between 10 and 20 years after diagnosis for most malignancies. Long-term survival is increasing for common hematologic malignancies, but late mortality is an ongoing issue. Further study of long-term outcomes in curable malignancies to determine the reason for these later decreases in survival is indicated.